PERANAN DINAS BINA MARGA DAN SUMBER DAYA AIR DALAM MENANGANI MASALAH BANJIR TAHUN 2014 (Studi Kasus Perumahan Graha Fauzan Asri) - Hendika Elfani Azlan; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru is the capital of Riau province who have serious problems with waterlogging and flooding at any time of the rainy season. Puddles usually occurs in areas of the drainage system is not functioning properly. While flooding is generally found in the area adjacent to the river flow. One of the flooded areas are quite alarming in the district of Bukit Raya from 2012 s / d 2013 there were at Graha Asri Village Fauzan Tangkerang Labuai. In carrying out the functions of government, one of the ways the City of dealing with the problem is to provide assistance in the form of long-term flood management, dredging the river. The purpose of this study was to determine the role of the Department of Highways and Water Resources as the City Government agencies Addressing Flood In 2014 at Graha Asri Fauzan and examines the factors supporting and inhibiting the realization of handling.In this paper the authors study using qualitative analysis. While data analysis technique used is descriptive analysis of spoken words or behavior that can be observed from those studied. Based on the results of research conducted and followed by analyzing the data obtained by direct interviews with informants to produce 3 role in carrying out the implementation of government functions: (1) The role as a provider of public services, general services performed for the public who made the Department of Highways and Resources Air power in the form of the provision of administrative services. (2) The role as Executive Function Regulation, ie all flood mitigation work done by Regional Regulation No. 10 Year 2006 Pekanbaru on Water Resources and Infiltration Wells. (3) The role as Executive Planning and Coordination, the general handling of the flood which carried out the dredging of the River Sail which of the planning and the implementation is done by the Department of Highways and Water Resources in coordination with the village and sub-district. And in the implementation of the process there are factors that affect the supporting and workmanship.Judging from these three roles, some disadvantages and advantages that made the Department of Highways and Water Resources Pekanbaru in addressing the problem of flooding in Fauzan Graha Asri housing in the district of Bukit Raya namely the lack, not the passage of cooperation between donor agencies and the advantages of building permits is fast responsiveness of Highways and Water Resources in dealing with the flooding problem Sail River dredging solutions.Keywords: Role, Flood, Government